2021
DOI: 10.1111/wvn.12526
|View full text |Cite
|
Sign up to set email alerts
|

Admission Braden Scale Score as an Early Independent Predictor of In‐Hospital Mortality Among Inpatients With COVID‐19: A Retrospective Cohort Study

Abstract: Background: The COVID-19 pandemic has put a strain on health systems. Predictors of adverse outcomes need to be investigated to properly manage COVID-19 patients. The Braden Scale (BS), commonly used for the assessment of pressure ulcer risk, has recently been proposed to identify frailty.Objective: To investigate the predictive utility of the BS for prediction of in-hospital mortality in a cohort of COVID-19 patients admitted to non-ICU wards.Methods: We conducted a retrospective single-center cohort study ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Some other studies also found the Barthel Index was associated with the mortality of COVID-19 patients ( 33 35 ), but none of them offered a simple and practical evaluation method. Another study reported that the Barthel Index was not a significant predictor ( P = 0.128), but that may be due to its small sample size ( n = 146) ( 36 ). According to the ROC curve, the AUC of the Barthel Index was 0.764 (95%CI: 0.701–0.827), which was different from the reference (0.5), and the value of the Barthel Index was 76.5 when the Youden Index was maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies also found the Barthel Index was associated with the mortality of COVID-19 patients ( 33 35 ), but none of them offered a simple and practical evaluation method. Another study reported that the Barthel Index was not a significant predictor ( P = 0.128), but that may be due to its small sample size ( n = 146) ( 36 ). According to the ROC curve, the AUC of the Barthel Index was 0.764 (95%CI: 0.701–0.827), which was different from the reference (0.5), and the value of the Barthel Index was 76.5 when the Youden Index was maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PI on admission had statistically lower BS scores (12.35±2.72 versus 16.53±3.6). Admission BS could be an easy predictive instrument for older adults because of its ability to be an indicator of frailty, the need for a rehabilitation facility and even mortality [21,22]. Despite these benefits of BS, previous studies reported particular limitations in its ability to predict PI due to missing parameters in its evaluation [23].…”
Section: Discussionmentioning
confidence: 99%
“…El uso de este instrumento es obligatorio en algunas instituciones hospitalarias. Este hecho ha facilitado la evaluación de su validez predictiva de mortalidad: en procesos médicos (23,24), procesos quirúrgicos (25,26), unidades de cuidados intensivos (27), o más recientemente en hospitalizaciones por COVID-19 (28). Algunos de estos estudios también hallaron validez predictiva de la escala de Braden sobre el aumento de días de estancia hospitalaria (23,24,29).…”
Section: Discussionunclassified